ENHANCING THE QUALITY OF LIFE FOR THE ELDERLY IN KOH CHAN SUBDISTRICT MUNICIPALITY,CHONBURI PROVINCE - ทุมาโต วิชุดา; Chotpittayanon, Natnicha (Journal of MCU Phetchaburi Review, 2026)
This research aims to : 1)Study the quality of life of the elderly in Ko Chan Subdistrict Municipality, Chonburi Province; 2)Examine the factors affecting their quality of life; and 3)Propose guidelines for promoting the quality of life of the elderly in Ko Chan Subdistrict Municipality. This study employed a quantitative research methodology. The sample consisted of 230 elderly individuals aged 60 years and above who had resided in Ko Chan Subdistrict Municipality for at least one year. A questionnaire was used as the research instrument, and the data were analyzed using statistical software. The statistical methods included descriptive statistics frequency, percentage, mean, and standard deviation and inferential statistics such as the t-test, f-test, and Pearson correlation analysis. The results revealed that : 1) The overall quality of life of the elderly in the areas of health, environment, society, economy, and education was at a high level. Similarly, information access, life security, and emotional well-being were also rated as high. 2) Factors influencing the quality of life of the elderly namely policies promoting health activities, social activities, occupational activities, and education were found to be at a high level overall. 3) Guidelines for promoting systematic quality of life planning for the elderly in Ko Chan Subdistrict Municipality should emphasize integration with health, education, and social development agencies to ensure continuity and comprehensive coverage across physical, economic, social, and psychological dimensions. The establishment of a “Community Elderly Quality of Life Development Center” is recommended as a learning hub for health promotion, physical and mental rehabilitation, and intergenerational knowledge exchange. Furthermore, the research findings should be used to inform budget allocation and local policy formulation, prioritizing projects that address the real needs of the elderly, such as improving environmental safety, organizing health promotion activities, and providing occupation training to support supplementary income.